Armut und Umweltschutz: Potenziale und Barrieren im urbanen Raum Westafrikas - Huber, Elisabeth (SSOAR, GESIS – Leibniz-Institut für Sozialwissenschaften e.V., 2020)
Abstract: The phenomenon of poverty and its impact on environmental pollution of urban spaces in West Africa. On the relation between environmental awareness and living conditions
10.14361/9783839451168
Keywords: Hochschulschrift; (thesoz)Westafrika; (thesoz)Umweltschutz; (thesoz)Abfallbeseitigung; (thesoz)Entsorgung; (thesoz)Umweltbewusstsein; (thesoz)Umweltverhalten; (thesoz)Armut; (thesoz)Armutsbekämpfung; (thesoz)Entwicklungsland; (thesoz)Burkina Faso; (thesoz)Mali; (thesoz)Stadtbevölkerung; (thesoz)Lebensbedingungen; (thesoz)Infrastruktur; (thesoz)Stadtplanung; (thesoz)Postkolonialismus; (thesoz)soziale Ungleichheit; Abwasserentsorgung; Environmental Sociology; Ethnologie; Ethnology; Handlungstheorie; Living Space; Mutually Supportive; Recht Auf Stadt; Right To City; Solidargemeinschaft; Umweltsoziologie; Umweltverschmutzung; Urban Space; Urban Studies; Urbaner Raum; Waste Disposal; Wohnraum; (Zielgruppe)Fachpublikum/ Wissenschaft; Bevölkerung; Abfallentsorgung; Stadt; Natur; Poverty; Environmental Awareness; West Africa; Postcolonialism; Environment Protection; Infrastructure; Living Conditions; Population; Urban Planning; City; Nature; Social Inequality; (BIC subject category)RNT; (BIC subject category)JFSG; (BISAC Subject Heading)SOC002010; (BIC subject category)JHMC; Umweltbewusstsein; Verhalten; Alltag; Armut; Abfallbeseitigung; Abwasserbeseitigung